“TIME — THE SUPREME JUDGE” - Mahmudova Gulsoraxon; Mannobov Abdumalik Mansurjon oʻgʻli (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article, written from the perspective of a 6th grade student from Uzbekistan, explores the profound importance of valuing time in our daily lives. It discusses how time, once lost, can never be regained, and how students who use their time wisely are able to achieve great goals, make their parents proud, and contribute meaningfully to their country.